Pengaruh Problem Based Learning Terhadap Higher Order Thingking (HOTS) Pada Pembelajaran Matematika Siswa - Novi Tari Simbolon S.Pd., M.Si; Jose Andreas Gandhi Sinaga S.Pd, M.Pd; Eduard; Br Tarigan, Hanna Tasya; Br Sembiring, Katarina Junenti (Al-Azkiya: Jurnal Pendidikan MI/SD, 2025)
In the modern era of education, the development of Higher Order Thinking Skills (HOTS) is very important. Therefore, this study aims to explore the effect of the Problem Based Learning (PBL) learning model on improving students' HOTS in mathematics learning. By implementing PBL in mathematics learning, it is expected that students will not only be able to understand concepts but also be able to apply them in more complex and contextual situations. The purpose of this study is to analyze the effectiveness of PBL in improving elementary school students' HOTS. This study will involve students from grade V of elementary school, using a quasi-experimental method. Data will be ollectedthrough a specially designed HOTS test and in-depth interviews with students and teachers. The results of this study are expected to find a positive relationship between the implementation of PBL and the improvement of students' HOTS in mathematics learning. The findings of this study also contribute to providing information related to trends nd heterogeneity of research related to the implementation of PBL on mathematical HOTS in Indonesia so that it is expected to be a recommendation and idea for further research.